Why So Few Women Directors in Top UK Boardrooms? Evidence and Theoretical Explanations - Singh, Val; Vinnicombe, Susan (Blackwell Publishing Ltd, 2004)
Using evidence from a survey of women directors in FTSE 100 companies, this paper considers possible explanations for the persistent homogeneity of top UK boards. Only 61 per cent of the top 100 companies had female directors in 2002, down from 64 per cent in 1999. Women held only 3 per cent of executive (= US inside) directorships, and there were only 15 women executive directors in total. Explanations usually include women's lack of ambition, lack of experience and lack of commitment. These have been disproved by research, but underlying theories of social exclusion may provide insight into this persistent phenomenon.